Genetics and genomics of animal behaviour and welfare-Challenges and possibilities - Jensen, P; Buitenhuis, B; Kjaer, J; Zanella, A; Mormede, P; Pizzari, T (2008)
Traditionally, the contribution of applied ethology to animal welfare science has concentrated on understanding the reactions of animals to their housing conditions. Domestication has had small effects on fundamental aspects of animal behaviour, and therefore, the needs of present day domesticated animals are closely related to the evolutionary history of the ancestors. However, the last decades have seen an unprecedented intensification of selection for increased production, which has significant side-effects on behaviour and welfare. Understanding the nature of such side-effects have therefore emerged as a central problem to animal welfare science. Modern genetics and genomics offer tools for such research, and this review outlines some of the available methods and how these have been, and could be, used to enrich animal welfare science. An outline is given on traditional genetic selection methods applied on behaviour and welfare related variables. Significant improvements in levels of fearfulness and abnormal behaviour have been achieved by selecting populations against these traits. As a next step, it is necessary to map the loci involved in affecting these traits, and quantitative trait locus (QTL) analysis have been used for this. An overview of QTL-analyses of welfare related traits in different species is given, including how this analysis has provided new insights into the genetic architecture of the stress response. Beyond allelic differences, which can be mapped with QTL-analysis, welfare related biological responses may be mediated by acquired modifications in expression levels of genes and gene complexes. This can be analysed with cDNA microarray technology, and a review of relevant work in this respect is given. Many of the changes in genetic control mechanisms observed during selection are results of evolutionary responses, for example related to sexual selection. An overview with a genetic perspective is provided of this often neglected aspect of domestication in relation to animal welfare problems. It is concluded that modern selection of farm animals pose a serious challenge to animal welfare, but also previously unknown possibilities to improve welfare by using high precision breeding techniques. © 2008 Elsevier B.V. All rights reserved.